Wirelessness radical empiricism in network cultures - Mackenzie, Adrian, 1962- (MIT Press, 2010)
This title provides an account of the sensations associated with being entangled with wireless technologies that draws on the philosophical techniques of William James's radical empiricism.
Keywords: Wireless communication systems -- Social aspects.; Wireless communication systems -- Philosophy.; Information society.; Empiricism.; elektronické knihy; electronic books